Figurative Language Used In Nf Rap Songs Lyrics On The Album The Search - Subekti, Wakhid; Cicih Nuraeni; Delis Meta Tiana (CV. Kalimasada Group Profesional, 2023)
This writer discusses about an analysis of figurative language in NF rap songs on the album The search. The purpose of this research to find the types of figurative language and the most dominant types of figurative language in NF songs on the album The search. This research applied descriptive qualitative analysis as the research type. The data was taken from the lyrics of NF songs on the album The Search. The entire data is analyzed through describing object, collecting data, analyzing and then conclusion. The writer found sixty-two figurative languages used in eighteen songs on the album The Search. There are twenty hyperboles (32,26%), sixteen paradoxes (25,81%), ten personifications (16,13%), seven similes (11,29%), six metaphors (9,68%), one metonymy (1,61%) one symbolism (1,61%) and one irony (1,61%). The most dominant figurative language used in the eighteen songs is hyperbole with twenty (32,26%) used. The conclusion figurative language is another way of conveying meaning differently. hyperbole is the most used because NF uses a lot of exaggerated words to express what he feels. NF uses emotional and honest rapping to describe his feelings, giving listeners a strong and meaningful connection to his life story.